Міграція та її вплив на економіку України - Базан, А. В.; Bazan, A.; Яковенко, Р. В.; Yakovenko, R. (Кіровоград : „Поліграф-сервіс”, 2014)
Проаналізовано сутність, джерела та причини міграції робочої сили. Визначено тенденції міграції в Україні. Запропоновано шляхи оптимізації наявного стану з метою поліпшення економічної ситуації. The essence, sources and causes of labour migration are analyzed. The trends of migration in Ukraine are determined. The ways of optimization of the present state are proposed in order to improve the economic situation.
Migration and its impact on the Ukrainian economy
Keywords: міграція; демографічні процеси; трудова міграція; біженці; державна міграційна політика; migration; demographic processes; labour migration; refugees; national migration policy